On the shores of politics: Sea, solidarity and the Ships to Gaza. (August 2019) - Kosmatopoulos, Nikolas
In this article, I focus attention on the sea as a space for today's solidarity politics. Following the Ships to Gaza as they headed to breach the Israeli embargo of the seaside enclave, I explore the largely understudied relationship between the politics of solidarity and the materiality of the sea. I ask: What are the wider implications for politics and theory when the global solidarity movement turns to the sea to protest the occupation in Palestine and provide aid to the besieged population in Gaza? I suggest the term "terraqueous solidarities" to define grassroots political movements that take to the sea to practice solidarity with those resisting contemporary forms of colonial enclosure and state oppression. I argue that sea-based solidarity inadvertently crafts a novel space for solidarity politics. Within this space I identify the shore as the dynamic interface between forces of territorialization and practices of solidarity. Echoing Rancière, and looking at the shores of politics from the militarized coast off Gaza to the Greek ports from where the Ships sailed, I explore three iterations of the shore, in both material and metaphorical sense, which contribute in forging new relationships between the topoi of politics and the politics of utopia.